Photodegradation of Polyisobutylene Film by Addition of Tris(a-thiopicoline anilide) with Cobalt(III), Manganese(III) and Iron(III) - Handa, S.P.; Vasisht, S.L.; Singh, Avinash; Narayan, Sat (Asian Journal of Chemistry, 2010)
The addition of tris(a-thiopicoline anilide) with manganese(III) (TPAM) cobalt(III) (TPAC) and iron (TPAF) sensitized photo oxidative degradation of polyisobutylene (PIB) film. It was found that photo degradation of the polymer was affected by the kind of metal used. Ultraviolet and infrared absorption spectra have been employed to substantiate a mechanism of degradation process which does not involve abstraction of the polymer, but direct cleavage of the polymer backbone and presence of initiating radicals of TPAM, TPAC at the sites of scission. The chelate TPAF shows the best performance of a photo sensitizer by furnishing the chain initiating free radicals.